Peran Strategi, Sumber Daya serta Perubahan Teknologi dan Lingkungan Terhadap Penciptaan Keunggulan Kompetitif yang Berkesinambungan - Aisyah, Mimin Nur (Jurnal Ekonomi dan Pendidikan, 2012)
Creating a sustainable competitive advantage is a crucial factor in strategic management. With the competitive advantage, an organization will be able to continue its operation, win the competition, and achieve its goals. Strategy, resources, and technological & environmental changes are key factors that should be considered in building a sustainable competitive advantage. Strategy theorized the organization methods to compete successfully in its business. The strategies formulated to achieve competitive advantage includes overall low cost, differentiation, and focus strategy. Business that mix the cost and differentiation strategies has proved to achieve the highest performance. However, the variation in resources accumulation has become the core of strategy and gives significant contribution in building the competitive advantage. The choice of strategy is restricted by the number of resources available and how fast the organization acquires new resources. The Resources based View (RBV) provides a good explanation for this condition. New technology, the changes of customer demands, and the rise of newcomers provide significant changes in business competitive environment. They also affect strategic changes and sources of competitive advantage. The organizations will survive and succeed if they able to change as fast as or even faster than business environmental changes.